The Influence of Good Corporate Governance and Capital Structure on Firm Value: The Mediation Role of Financial Performance - Ridwan Nurazi; Intan Zoraya; Akram Harmoni Wiardi (Media Ekonomi dan Manajemen, 2020)
The objective of this study is empirically identify the impacts of Good Corporate Governance and capital structure on firm value with financial performance as intervening variable. We operate quantitative approach within the scope of manufacturing company of metal, chemical, and plastic packaging sector which listed in Indonesia Stock Exchange during the 2017-2018 periods as the population. Samples are chosen by purposive sampling method inwhich the company must report the financial statement in a row, obtained 79 observations. The data analysis technique used is financial ratio analysis to determine the condition of the business financial ratios of the variables studied. Data were analyzed using multiple linear regression analysis. The result shows that corporate governance and capital structure influence the firm value, moreover the use of institutional ownership ratio and capital structure will increase the value of the firm. The result also shows that the impact of Corporate governance and capital structure on the company value are mediated by financial performance. It means that the value of the firm can increase if the company able became an effective monitoring tool.